Probing the character of ultra-fast dislocations - Ruestes, Carlos Javier (2015)
Plasticity is often controlled by dislocation motion, which was first measured for low pressure, low strain rate conditions decades ago. However, many applications require knowledge of dislocation motion at high stress conditions where the data are sparse, and come from indirect measurements dominated by the effect of dislocation density rather than velocity. Here we make predictions based on atomistic simulations that form the basis for a new approach to measure dislocation velocities directly at extreme conditions using three steps: create prismatic dislocation loops in a near-surface region using nanoindentation, drive the dislocations with a shockwave, and use electron microscopy to determine how far the dislocations moved and thus their velocity at extreme stress and strain rate conditions. We report on atomistic simulations of tantalum that make detailed predictions of dislocation flow, and find that the approach is feasible and can uncover an exciting range of phenomena, such as transonic dislocations and a novel form of loop stretching. The simulated configuration enables a new class of experiments to probe average dislocation velocity at very high applied shear stress.